Efektivitas Pengelolaan Pajak Bumi dan Bangunan (PBB) - Tribuana, Putri Cahyani; Feriyanto, Oon (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This study examines the management of Land and Building Tax (PBB) in Tanjungwangi Village, where the realization rate remains below 50% of the target, affecting regional revenue. The purpose of this research is to analyze how PBB is managed, identify factors influencing the effectiveness of village performance, and explore existing obstacles. This reseacrh use a descriptive qualitative method was used, with data collected through observation, interviews, and documentation. The findings indicate that PBB management aligns with government policies but still faces several challenges, both internal (motivation, leadership, discipline) and external (community economic conditions, lack of socialization, geographical barriers, and inaccurate data). Recommendations include officer training, increased public outreach, and updating PBB data.